2013
DOI: 10.1210/jc.2012-4205
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Method for Determining the Renal Threshold for Glucose Excretion in Untreated and Canagliflozin-treated Subjects With Type 2 Diabetes Mellitus

Abstract: Context:The stepwise hyperglycemic clamp procedure (SHCP) is the gold standard for measuring the renal threshold for glucose excretion (RTG), but its use is limited to small studies in specialized laboratories.Objective:The objective of the study was to validate a new method for determining RTG using data obtained during a mixed-meal tolerance test (MMTT) in untreated and canagliflozin-treated subjects with type 2 diabetes mellitus (T2DM).Design:This was an open-label study with 2 sequential parts.Setting:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 15 publications
3
88
0
Order By: Relevance
“…The effects of SGLT2 inhibitors on renal glucose kinetics were assessed using controlled glucose infusion experiments in rats (13) and humans (14,15). These experiments showed that SGLT2 inhibition leads to a reduction in T M G and RT G while maintaining a threshold-like relationship between PG and the UGE rate (Fig.…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of SGLT2 inhibitors on renal glucose kinetics were assessed using controlled glucose infusion experiments in rats (13) and humans (14,15). These experiments showed that SGLT2 inhibition leads to a reduction in T M G and RT G while maintaining a threshold-like relationship between PG and the UGE rate (Fig.…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 99%
“…In such patients, SGLT2 inhibitors can be used as monotherapy, and in clinical trials, compared with placebo/active comparator, they lowered fasting PG (FPG) by 20- Results (mean 6 SE) from a graded glucose infusion study in Zucker diabetic fatty (ZDF) rats (13). Right panel: Results (mean 6 SD) from a stepwise hyperglycemic clamp study in human subjects with T2D (15). In both studies, canagliflozin treatment produces a left shift in the relationship between blood glucose and UGE with no apparent change in the slope, leading to a reduction in RT G .…”
Section: Monotherapymentioning
confidence: 99%
“…Canagliflozin reduces blood glucose levels through an insulin-independent mechanism by lowering the renal threshold for glucose and increasing urinary glucose excretion, which results in a mild osmotic diuresis and net caloric loss (11)(12)(13). In phase 3 studies, canagliflozin improved glycemic control, reduced body weight and blood pressure, and was generally well tolerated across a broad range of patients with type 2 diabetes (10,14).…”
mentioning
confidence: 99%
“…An inherited deficiency of SGLT2 can produce renal glucosuria, with some affected individuals excreting as much as 100 g of urinary glucose per day (5). Canagliflozin is an orally active inhibitor of SGLT2 that reduces proximal tubular glucose reabsorption and increases urinary glucose excretion (10)(11)(12)(13). Treatment produces a significant loss of glucose, with beneficial effects on glycemic control, body weight, and blood pressure (12,(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%